The Chilean Medium-Sized Port Companies in Knowledge Management: Diagnosis, Challenges and Trends - Cordova-Gonzalez, F; Duran-San Martin, C (Elsevier B.V., 2015)
This paper presents a study of the behaviour of companies participating in Chilean ports of medium size in the processes of creation, transmission and dissemination of knowledge. A diagnosis of the current situation and the identification of the relevant requirements of knowledge management, through surveys and interviews, were carried out by the main actors of the community. The knowledge management processes related to the intellectual, structural, and social capital that have been developed by the different actors involved in the medium-sized port communities are identified. Also, the stage of externalization of knowledge is examined to find the critical factors of knowledge transference. Meanwhile, the role of the knowledge creation process in innovation, generated by public a private institutional systems, is acknowledged. The results of the analysis show that the competitive and efficient management of a port is mainly based on: knowledge sharing and dissemination, collaboration and team work, knowledge storage and best practices. Then, a model that establishes the stages of development for achieving knowledge management in medium-sized port companies is proposed. With respect to information management and learning, the need of a virtual space with available and continuously updated information and knowledge, that will be useful to the members of this community, has been detected. Finally, the challenges and trends related to integrated logistics, port community and collaborative learning networks, logistic platforms and inter-modality, and creation and dissemination of knowledge are observed. © 2015 Published by Elsevier B.V.